RADIKALISME VERSUS ISLAM RAHMA - Abbas, Abbas (P3M STAIN Sorong, 2015)
Islamic doctrine is viewed as rahmatan lil alamin. But it still needs big question. Then it is not only based on the application aspect, but also rahmatan lil alaminâs consept. Besides as academic intelectual activities, quarrying the rahmatan lil alaminâs consept, this information era, also by the future observer state that involvement of the academic intelectual workings urgent dan to be needed to overcome the lifeâs problems nowadays. So radicalism and terrorism in this view, are not separated with rahmatan lil alamin of Islamic doctrine views. This writing discourses the central theme, namely; As Islamic doctrine and its relevance of local wisdem, how is the rahmatan lil alaminâs consept. The study answers questions: First, what are radicalism and terrorism term? Second, as a big Islam vision or mision, how is the Rahmatan lil alamimâs concept? Thirt, how is the local wisdem (Bugisnessâs ethnic) as culture basis humanity? Fourth, how is the local culture development and Islam in the context of amar makruf nahi munkar: terrorism and radicalism bid to prevention?. The last, this writing gives birth to viewings that Islam concept is rahmatan lil alamin, have views about humanity, freedom of expression, wisdom, ect.